Implementación de una empresa productora de hortalizas orgánicas semipreparadas en la parroquia Purunuma cantón Gonzanamá y su comercialización en la provincia de Loja. - Jumbo Montoya, Leydy Beatriz (2012)
currently the parish of Canton Purunuma Gonzanamá is affected by a marked downturn in the productive, being a barrier to sustainable development and to compete in the province of Loja. That is why the new generation of professionals we have to make efforts to create small innovative companies, occupying the local workforce, with resources in the area and with products that may hit the market in top condition, quality and price. For these reasons this project is intended to assist with the implementation of a company that will create some jobs, leverage existing resources, creating economic value added and put into practice the knowledge acquired for the benefit of a society that needs to their new professionals are inserted into the economic and productive life. From here the real need to produce goods and services, being enterprising and facing the grave crisis facing our country, being convenient to carry out and execute our thesis project entitled: "Implementation of a producer of semi-prepared organic vegetables in the Parish Purunuma (Canton Gonzanamá) and marketing in the Province of Loja "it contributes to the development of the county and province of Loja. This project aims to produce vegetables using an engineering process will get a good quality product and competitive prices, this adds to the inputs used which ensures that you have a very good reception in the consumer market, on the other vegetables are very important and are good for health, with an internationally recognized high nutritional content, which opens the door to see the possibility in the near future so they can export. For this is a descriptive study and market technician, a study was made of the company organizational, financial study, through indicators such as Net Present Value (NPV) giving a positive result it is $ 30,223, 81 This indicates a greater initial investment, internal rate of return (IRR) of 19.22% which is therefore the project is accepted, Benefit Cost Ratio of 1.25 indicates that for every dollar invested there 0.25 utility cents, Capital Recovery Period (PR / C) is 5 years, 10 months and 13 days, the sensitivity analysis in the increased cost is 7.83% shows that the project is sensitive, so does the sensitivity analysis with declining revenues the value obtained is 6.28% this shows that the project is sensitive. At the end of this research disclosed conclusions and recommendations arising.